Sliding Wear Modeling of Artificial Rough Surfaces - Imam Syafa’at; Budi Setiyana; Muchammad Muchammad; Jamari Jamari (Chemical Engineering Diponegoro University, 2013)
Surface roughness plays an important role in machine design. In the micro-scale when two engineering surfaces are brought into contact, the real contact area occurs at isolated point of asperity. Wear is one of some effects of contacting surfaces. This paper presents a modeling of sliding wear at asperity level on the artificial rough surfaces. The surface roughness is represented by spherical asperities at the hemispherical pin that is developed from the existing model. The wear model is based on the simple analytical solution. The combination of Archard’s wear equation and finite element simulation is performed to predict the wear. Results show that the increasing of sliding distance give the increasing of wear depth, wear scar diameter and wear volume of the asperity. Wear at the center of the contacting rough surface is higher than the its surrounding. [Keywords: Rough Surface; Sliding Wea; Wear Scar Diameter; Wear Volume]